Unlocking the adaptation mechanisms of the oleaginous microalga Scenedesmus sp. BHU1 under elevated salt stress: a physiochemical, lipidomics and transcriptomics approach - Singh, Rahul Prasad; Yadav, Priya; Sharma, Himani; Kumar, Ajay; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Gupta, Rajan Kumar (Frontiers in Microbiology, 2024)
Microalgae are vital for their photosynthetic abilities, contributing significantly to global oxygen production, serving as a key trophic level in aquatic ecosystems, aiding in biofuel production, assisting in wastewater treatment, and facilitating the synthesis of valuable biochemicals. Despite these advantages, photosynthetic microalgae are sensitive to salt stress, which alters their physiochemical and metabolic status, ultimately reducing microalgal growth. This sensitivity highlights the importance of understanding the impact of elevated salt content on the physiochemical, metabolic, and transcriptomic profiling of Scenedesmus sp., areas that are not yet fully understood. Our findings indicate that elevated salt stress decreases photosynthetic efficiency and increases non-regulated photochemical quenching of photosystem II (PSII). Moreover, PSII-driven linear electron flow (LEF) decreased, whereas photosystem I (PSI)-driven cyclic electron flow (CEF) increased in salt-stressed cells. To better understand the electron flow from PSII to PSI under elevated salt treatment, we analyzed the excitation energy flux per reaction center (RC), per cross-section (CS), energy flux ratios, and the potential index of PSII. Additionally, flow cytometry graphs depict the viability assay of Scenedesmus sp. BHU1. Our observations further revealed an increase in biochemical attributes, such as stress biomarkers, osmoprotectants, and enzymatic antioxidants, which help scavenge reactive oxygen species (ROS) under salt stress. Intracellular cations (Na + and Ca2+) were increased, while K+ levels decreased, indicating mechanisms of cellular homeostasis under salt stress. UHPLC-HRMS-based lipidome analysis confirmed that increasing salt stress induces the hyperaccumulation of several fatty acids involved in adaptation. Moreover, transcriptome analysis revealed the upregulation of genes associated with PSI, glycolysis, starch metabolism, sucrose metabolism, and lipid accumulation under salt stress. In contrast, genes related to PSII and C3 carbon fixation were downregulated to mitigate the adverse effects of salt stress.